Rawi Khawarij dalam Sahih Al-Bukhari - Muhammad Nur Shiddiq (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2020)
This paper discusses the rites of khawarij hereditary in some hadith narations noticable in Sahi>h al-Bukhari. Among them name was ‘Imran ibn Hittan. Using a literary approach, this article reveals the dispute among hadith scholars whether or not to accept those rites. Ulama who reject the history of heresy experts had accused them as kufr. Whereas ulama who allow the history of bid'ah experts generally have clearrequirements. The requirement is that this narrator is not included in the rawi muttaham bi al-kidhb, and also his history does not call upon his bid'ah. This paper reveals a rawi named ‘Imran ibn Hittan, even though he was a Khawarij, was a thiqah. In his narratives found in Sahih al-Bukhari do not call on the bid'ah that he believes. So that the hadith which is narrated through ‘Imran ibn Hittan does not need to doubt its validity.",